Imaging of IgG4-related disease in the extracranial head and neck. Issue 136 (March 2021) - Dragan, Alina Denisa; Weller, Alexander; Lingam, Ravi Kumar
Highlights: IgG4 related disease is a new but well-defined pathological entity. The extracranial Head&Neck is the 2nd most common affected site, after the pancreas. On imaging, it can mimic malignant, inflammatory, or infectious diseases. Commonly involved sites have recognised patterns of disease. Suspicion on imaging can prompt the diagnostic workup for this condition. Abstract: Purpose: Immunoglobulin G4-related disease (IgG4-RD) is a newly defined fibro-inflammatory multisystemic condition defined by a triad of diagnostic criteria based on clinical presentation, biochemical and histopathological findings. Whereas some subsites of this disease have been well described in the literature so far (e.g. pancreas, kidneys, retroperitoneum, salivary glands), more recently identified anatomical sites of involvement in the head and neck are less well understood (e.g. nose, paranasal sinuses). Method: This pictorial review details the imaging appearances of extracranial IgG4-RD in the Head & Neck. Multimodality imaging appearance and features are presented, with reference to the published literature to date. Results: Following a subsite-based approach, we present both the most common and the more rarely encountered imaging patterns of IgG4-RD in the extracranial head and neck, along with the relevant differential diagnoses to consider. Our institutional experience not only cements what is already known in the existing literature on this topic, but also reveals new imaging features of IgG4-RD, notably in the sinonasal tract. Conclusions: This pictorial review of extracranial head & neck IgG4-RD will enable radiologists to recognise the features of this condition and propose it as a differential diagnosis to include alongside other probable entities. It establishes the place of the radiologist in the diagnosis and management of IgG4-RD.